Antioxidant Capacities of Flavones and Benefits in Oxidative-Stress Related Diseases - D. Catarino, Marcelo; M. Alves-Silva, Jorge; R. Pereira, Olivia; M. Cardoso, Susana (Current Topics in Medicinal Chemistry, 2015)
Flavonoids, a group of secondary metabolites widely distributed in the plant kingdom, have been acknowledged for their interesting medicinal properties. Among them, natural flavones, as well as some of their synthetic derivatives, have been shown to exhibit several biological activities, including antioxidant, anti-inflammatory, antitumor, anti-allergic, neuroprotective, cardioprotective and antimicrobial. The antioxidant properties of flavones allow them to demonstrate potential application as preventive and attenuating agents in oxidative stress, i.e., a biological condition that is closely associated to aging process and several diseases. Some flavones interfere in distinct oxidative-stress related events by directly reducing the levels of intracellular free radicals (hydroxyl, superoxide and nitric oxide) and/or of reactive species (e.g. hydrogen peroxide, peroxynitrite and hypochlorous acid) thus preventing their amplification and the consequent damage of other biomolecules such as lipids, proteins and DNA. Flavones can also hinder the activity of central free radical-producing enzymes, such as xanthine oxidase and nicotinamide adenine dinucleotide phosphate oxidase (NADPH-oxidase) or inducible nitric oxide synthase (iNOS) and can even modulate the intracellular levels of pro-oxidant and/or antioxidant enzymes. The evaluation of flavones antioxidant ability has been extensively determined in chemical or biological in vitro models, but in vivo therapy with individual flavones or with flavones-enriched extracts has also been reported. The present manuscript revises relevant studies focusing the preventive effects of flavones on stress-related diseases, namely the neurological and cardiovascular diseases, and diabetes and its associated complications.
Keywords: Antioxidant activity